2019
DOI: 10.1109/tim.2018.2871229
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Frequency Response Measurements of Voltage Transformers: An Approach Based on Quasi-Sinusoidal Volterra Models

Abstract: The most recent IEC standards about voltage transformers warn about nonlinearity, which may have significantly impact on the harmonic measurement performance. However, there is a lack of scientific literature about this topic: usually their characterization consists of frequency response measurements, which are clearly not able to capture the nonlinear behavior.In this paper, an innovative approach based on simplified frequency domain polynomial models developed by the authors is proposed. The method is applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 15 publications
0
36
0
Order By: Relevance
“…Similar to the case of CTs, also the metrological performance of conventional voltage transformers (VTs) employed for harmonic measurement is strictly related to their dynamic and nonlinear behavior [ 23 ]. In this respect, the authors of the present paper have shown that nonlinear behavioral models based on a simplified Volterra representation [ 24 , 25 ] can be used to accurately predict the secondary voltage spectrum from the primary side [ 26 ]. This enables a thorough characterization of VTs: linear and nonlinear effects can be separated, nonlinearities can be classified, and their individual impact on the overall metrological performance can be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the case of CTs, also the metrological performance of conventional voltage transformers (VTs) employed for harmonic measurement is strictly related to their dynamic and nonlinear behavior [ 23 ]. In this respect, the authors of the present paper have shown that nonlinear behavioral models based on a simplified Volterra representation [ 24 , 25 ] can be used to accurately predict the secondary voltage spectrum from the primary side [ 26 ]. This enables a thorough characterization of VTs: linear and nonlinear effects can be separated, nonlinearities can be classified, and their individual impact on the overall metrological performance can be studied.…”
Section: Introductionmentioning
confidence: 99%
“…The metrological performances of these sensors in presence of harmonic distortion significantly depend on their operating principles. In the particular case of the frequently used inductive instrument transformers (ITs), not negligible ratio and phase errors can be introduced both at low and high frequency harmonics [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In [5,6,8,9] the ITs characterizations performed under distorted conditions have highlighted errors up to some percent for the first 10-15 harmonics. In [10], some of the authors have shown that the current transformers (CTs) ratio and phase errors at power frequency can increase up to exceed their accuracy class limits in presence of modulated current signals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations